A highly sensitive fluorescent sensor for ammonia detection based on aggregation-induced emission luminogen-doped liquid crystals. Issue 39 (29th September 2022) - Zhan, Xiyun; Liu, Yanjun; Wang, Fei; Zhao, Dongyu; Yang, Kun-Lin; Luo, Dan
Abstract : A novel fluorescent sensor based on an AIEgen-doped LC system was developed for ammonia detection. The change of LC orientation can be induced in the presence of ammonia, leading to the variation of fluorescence intensity. Abstract : As a toxic substance, ammonia can cause serious irritation to the human respiratory system and lungs. Although many detection techniques have been reported, most of them have drawbacks, such as expensive devices and complex and time-consuming fabrication processes. Thus, it is important to develop a simple method for ammonia detection. In this paper, we demonstrate a highly sensitive fluorescent sensor for ammonia detection based on aggregation-induced emission luminogen-doped liquid crystals without the use of polarizers. The homeotropic orientation of the liquid crystals on a modified substrate can be disturbed by ammonia, resulting in the fluorescence intensity change of an aggregation-induced emission luminogen. This aggregation-induced emission luminogen-doped liquid crystal-based fluorescent sensor for ammonia detection exhibited a low detection limit of 5.4 ppm, which is 3 times lower than previously reported liquid crystal-based optical sensors. The detection range is also broad from 0 ppm to 1600 ppm. Meanwhile, this sensor can be applied to detect aqueous ammonia with a low limit of detection of 1.8 ppm. The proposed fluorescent sensor for ammonia detection based on an aggregation-induced emission luminogen-doped liquid crystal is highly sensitive, highly selective, simple, and low cost with wide potential applications in chemical and biological fields. This strategy of designing a liquid crystal fluorescent sensor provides an inspiring stage for other toxic chemical substrates by changing specific decorated molecules.